(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Banking is the backbone of every industry and technology plays an important role in every industry. The role of technology is increasing very rapidly day by day, which is also promoting the banking industry. Banking is one of the largest financial institutions which regularly explore the opportunity of technology to provide better customer services. Over the years, banking has transcended from a traditional brick-and mortar model of customers queuing for services in the banks to modern day banking where banks can be reached at any point for their services. In today’s business, technology has been the largest indicators of growth and competitiveness. The banking industry today is in the industry of its revolution. Information technology has basically been used under two different avenues in banking. One is communication and connectivity and other is business process. Today, banks have adopted wireless and mobile technology in their classroom to give their customers the freedom to pay off debts, arrange payments while stuck in traffic, get updates on various marketing efforts while at a party to provide more personal and intimate relationships. This paper examines consumer acceptance of a new electronic payment service as a mobile banking and positive and negative factors influencing the acceptance of mobile banks in India.